Assessment of a standardized rubric to evaluate student presentations - Hassan Mohamed Abouelkheir (Wolters Kluwer Medknow Publications, 2017)
Introduction: Design of a standardized rubric for measuring student performance in presentations is a critical issue. Materials and Methods: Thirty male students (Group I) and thirty female students (Group II) participated in this study. Likert scale was used (excellent, good, average, and unsatisfactory). It was used against the itemized criteria (introduction, content, slide arrangement, written work, delivery and use of references). Results: high Cronbach's alpha reliability of the rubric was found in either Group I (0.945) or Group II (0.878) where it is slightly higher in the Group I at the 5% level. Corrected item-total correlation for delivery variable in Group I is very weak (0.222) while correlation for reference variable in Group II was averaged (0.525). Conclusion: Group II showed higher delivery performance than Group I as Group I had a lack of English language proficiency, while in Group II, they miss reference citation which can be corrected.